Qualitative Behavior of Cosmological Model with Cosmic Strings and Minimally Interacting Dark Energy - Mete, V. G.; Deshmukh, V. S.; Kapse, D. V. (Journal of Scientific Research, 2024)
This article is devoted to the study of Kaluza-Klein space-time filled with cosmic string and attractive massive scalar field in the presence of minimally interacting dark energy in general relativity. Some physically significant conditions have been utilized to obtain a deterministic solution of the field equations. The behavior of cosmological parameters such as volume, scalar field, deceleration parameter, equation of state (EoS) parameter, statefinder parameter, Om diagnostic are discussed. It is also worth noting that the conclusions of the cosmological parameter are consistent with modern observational data.